2017
DOI: 10.1093/cid/cix355
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Adding a Single Low Dose of Primaquine to the Treatment of Adult Patients With Plasmodium falciparum Malaria in Senegal, to Reduce Gametocyte Carriage: A Randomized Controlled Trial

Abstract: SummaryAdding low-dose primaquine to malaria treatment reduced gametocyte carriage by 73%. Patients who received primaquine had more frequent hemoglobinuria and there was a greater reduction in haemoglobin concentration in G6PD-deficient patients. One patient who received primaquine developed moderately severe anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 32 publications
(39 reference statements)
2
44
2
Order By: Relevance
“…Ten new publications described seven new trials published since the last revision ( Dicko 2016 ; Gonçalves 2016a ; Gonçalves 2016b ; Mwaiswelo 2016 ; Okebe 2016 ; Lin 2017 ; Tine 2017 ). The Goncalves study is regarded as two trials because the two phases had different inclusion criteria ( Gonçalves 2016a ; Gonçalves 2016b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten new publications described seven new trials published since the last revision ( Dicko 2016 ; Gonçalves 2016a ; Gonçalves 2016b ; Mwaiswelo 2016 ; Okebe 2016 ; Lin 2017 ; Tine 2017 ). The Goncalves study is regarded as two trials because the two phases had different inclusion criteria ( Gonçalves 2016a ; Gonçalves 2016b ).…”
Section: Resultsmentioning
confidence: 99%
“…Five trials with artemisinin partners reported area under curve (AUC) or log(10)AUC as a summary combined measure of gametocyte prevalence and density over time, using PCR estimates of density ( Shekalaghe 2007 ; Eziefula 2013 ; Dicko 2016 ; Gonçalves 2016b ; Tine 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Occassionally, moderate or severe transient anaemia was observed after a single PQ-dose of 0.75 mg/kg [ 16 ]. More recently, the safety of the 0.25 mg/kg PQ dose was reported as ancillary analysis after a malaria elimination campaign on the Thai-Myanmar border [ 24 ], in a gametocyte clearance efficacy study in Tanzania [ 25 ], and in a randomized controlled safety trial in Senegal [ 26 ]. The first two studies observed mean relative reductions in hemoglobin of 4–8% 5–8 days after 0.25 mg/kg PQ in a subpopulation of G6PDd participants [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…While all studies suggested the WHO-recommended PQ dose was safe, only the study from Tine et al . intensively monitored G6PDd individuals who have a higher risk of hemolysis [ 26 ]. Markers of hemolysis, including reticulocyte counts, lactate dehydrogenase (LDH), haptoglobin and bilirubin concentrations were not examined.…”
Section: Introductionmentioning
confidence: 99%